1988
DOI: 10.1055/s-0038-1642759
|View full text |Cite
|
Sign up to set email alerts
|

ADP Plays a Key Role in Thrombogenesis in Rats

Abstract: SummaryThe relative importance of ADP, arachidonic acid metabolites and serotonin as thrombogenic factors was evaluated in rats by comparing, after oral administration, the effects of two inhibitors of ADP-induced platelet aggregation (ticlopidine and PCR 4099), three cyclo-oxygenase inhibitors (aspirin, triflusal and indobufen) and a selective serotonin 5HT2 receptor antagonist (ketanserin) on platelet aggregation, in four platelet-dependent thrombosis models and on bleeding time. Platelet aggregation induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 31 publications
7
49
0
Order By: Relevance
“…Ticlopidine is a thienopyridine that has been shown to selectively inhibit the response to ADP of human and rat platelets [8][9][10]. A derivative of ticlopidine, clopidogrel, has been shown to have a stronger inhibitory effect on platelet aggregation stimulated by ADP and other agonists compared with ticlopidine [11].…”
Section: Introductionmentioning
confidence: 99%
“…Ticlopidine is a thienopyridine that has been shown to selectively inhibit the response to ADP of human and rat platelets [8][9][10]. A derivative of ticlopidine, clopidogrel, has been shown to have a stronger inhibitory effect on platelet aggregation stimulated by ADP and other agonists compared with ticlopidine [11].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have suggested that ADP, a common agonist, plays an important role in the initiation and progression of arterial thrombus formation (4)(5)(6). A potent inhibitor of ADP-induced platelet aggregation would therefore be of particular interest in searching for antithrombotic agents.…”
mentioning
confidence: 99%
“…The latter observation appears to indicate that clopidogrel suppressed thrombogenesis caused by the photochemical reaction, since Maffrand et al (21) have described that ADP plays a key role in thrombogenesis in the rat, and another ADP-induced platelet aggregation inhibitor, ticlopidine, suppressed PIT in the rat femoral artery (12).…”
Section: Discussionmentioning
confidence: 99%